Safety and efficacy of endoscopic retrograde cholangiopancreatography in previously treated liver cancer patients: a survival analysis - Li, Hong-Yu; Jia, Lijun; Du, Wujun; Huang, Xiao-Rong (Frontiers in Oncology, 2023)
Background and Aim: The prognosis and medication response for liver malignancies are both dismal and highly heterogeneous. For this diverse malignancy, multimodality therapies such as drugs, surgical management, and/or liver transplantation are available. Biliary complications remain a major problem after liver cancer treatment especially in those patients who undergo liver transplantation for their end stage liver disease. Although, most biliary complications can be successfully managed with endoscopic retrograde cholangiopancreatography. However, biliary complications still considered an important factor influencing long-term results in liver cancer treatment patients. The aim of this study was to evaluate the effect of biliary complications on the overall patient's survival rate after the endoscopic retrograde cholangiopancreatography. Material and Methods: We retrospectively analyzed data of consecutive patients who were treated for liver cancer at our tertiary care hospital from January 2015 to July 2020. We focused on the biliary complications and procedural data, including post-endoscopic retrograde cholangiopancreatography complications, survival rate, and complementary or alternative treatments to endoscopic retrograde cholangiopancreatography. Results: We identified 967 cases (mean age 49; range 11-75), 84% men. During the mean follow up of 25 months (range 1 to 66 months), 102 patients developed biliary complications; 68/102 underwent 141 therapeutics endoscopic retrograde cholangiopancreatography procedures. The rest 34/102 patients were managed with percutaneous transhepatic cholangiography, conservative management, and/or surgery. Post-endoscopic retrograde cholangiopancreatography complications occurred in 79.4%, including anastomotic strictures in 25, non-anastomotic strictures in 5, stones in 5, cholangitis in 4, post-sphinctretomy bleeding in 3, pancreatitis in 2, and bile leakage in 1 patient. Seven (13.0%) patients died after ERCP due to multiple organ dysfunction syndrome. Although the survival rate of patients who underwent ERCP and those without ERCP was similar, patients with biliary complications fared significant worse. Conclusion: Although endoscopic retrograde cholangiopancreatography is useful for the management of post liver cancer treatment biliary complications; the need for multiple rounds of endoscopic retrograde cholangiopancreatography and even post endoscopic retrograde cholangiopancreatography complications is relatively high, and often results in increased mortality. However, the survival following endoscopic or surgical therapy in liver cancer treatment patients is similar.